2008
DOI: 10.1111/j.1365-2958.2008.06456.x
|View full text |Cite
|
Sign up to set email alerts
|

A conserved domain of previously unknown function in Gap1 mediates protein–protein interaction and is required for biogenesis of a serine‐rich streptococcal adhesin

Abstract: SummaryFap1-like serine-rich proteins are a new family of bacterial adhesins found in a variety of streptococci and staphylococci that have been implicated in bacterial pathogenesis. A gene cluster encoding glycosyltransferases and accessory Sec components is required for Fap1 glycosylation and biogenesis in Streptococcus parasanguinis. Here we report that the glycosylation-associated protein, Gap1, contributes to glycosylation and biogenesis of Fap1 by interacting with another glycosylation-associated protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 44 publications
1
48
0
Order By: Relevance
“…mAbD10 is a glycan-specific antibody, and mAbF51 reacts with mature Fap1. Previous studies had revealed that the gap1 and gap3 mutants exhibited similar phenotypes in Fap1 biogenesis; both produce a 470-kDa high-molecular-weight (HMW) Fap1 precursor (18). A similar HMW Fap1 protein was also detected in the secA2 mutant by Western blot analyses using mAbE42 (Fig.…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…mAbD10 is a glycan-specific antibody, and mAbF51 reacts with mature Fap1. Previous studies had revealed that the gap1 and gap3 mutants exhibited similar phenotypes in Fap1 biogenesis; both produce a 470-kDa high-molecular-weight (HMW) Fap1 precursor (18). A similar HMW Fap1 protein was also detected in the secA2 mutant by Western blot analyses using mAbE42 (Fig.…”
Section: Resultsmentioning
confidence: 67%
“…A number of accessory Sec components have been identified and implicated in secretion of SRRPs (1,7,18,19,22,24,26,30,35,36); however, the precise roles of each component have yet to be defined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have proven that TPR, a scaffold for the recognition of partner proteins or acceptor peptides, is crucial for the activity of OGTs (9,60). Similar to TPR, the DUF1975 domain of GtfA has also been implicated in mediating protein-protein interactions and is essential for the glycosylation of SRRPs (25,61). In our docking model, we found that the two most N-terminal residues of SRR1, Asn-1Ј and Ser-2Ј, form sidechain hydrogen bonds with residues Asn-98, Arg-103, and Tyr-116 of DUF1975 (Fig.…”
Section: Duf1975 Is Required For Binding Ofmentioning
confidence: 99%